BIO095: Foundation Biology II / Centre of Foundation Studies - UiTM, Centre of Foundation Studies (2017)
This course contains eight chapters which include genetic inheritance and genetic control, gene technology, homeostasis, reproductive system, hormonal and nervous communication, circulatory system, immune system and respiratory system. These topics examine the inheritance, gene expression and regulation, DNA technology and physiology of humans and selected organisms.